Energy Data Visualization Requires Additional Approaches to Continue to be Relevant in a World with Greater Low-Carbon Generation - Grant Wilson, I. A. (Frontiers in Energy Research, 2016)
The hypothesis described in this article proposes that energy visualisation diagrams commonly used need additional changes to continue to be relevant in a world with greater low-carbon generation. The diagrams that display national energy data are influenced by the properties of the type of energy being displayed, which in most cases has historically meant fossil fuels, nuclear fuels or hydro. As many energy systems throughout the world increase their use of electricity from wind or solar based renewables, a more granular display of energy data in the time domain is required. This article also introduces the shared axes energy diagram that provides a simple and powerful way in which to compare the scale and seasonality of the demands and supplies of an energy system. This aims to complement rather than replace existing diagrams, and has an additional benefit of promoting a whole systems approach to energy systems, as differing energy vectors such as natural gas, transport fuels, and electricity can all be displayed together. This in particular, is useful to both policy makers and to industry, to build a visual foundation for a whole systems narrative, which provides a basis for discussion of the synergies and opportunities across and between different energy vectors and demands. The diagram’s ability to wrap a sense of scale around a whole energy system in a simple way is thought to explain its growing popularity.